Reducing cold-start emission from internal combustion engines by means of thermal energy storage system - (:unkn) unknown (PERGAMON-ELSEVIER SCIENCE LTD, 2009)
increasing environmental pollutions is an important problem appearing at cold start of internal combustion engines. Developments of new devices that solve this problem are an extremely urgent need especially for cold regions. In this study, a developed experimental sample of thermal energy storage system (TESS) for pre-heating of internal combustion engines has been designed and tested. The development thermal energy storage device (TESD) works on the effect of absorption and rejection of heat during the solid-liquid phase change of heat storage material (Na2SO4 center dot 10H(2)O). The TESS has been applied to a gasoline engine at 2 degrees C temperature and 1 atm pressure. Charging and discharging time of the TESD are about 500 and 600 s, respectively and temperature of engine is increased 17.4 degrees C averagely with pre-heating. Maximum thermal efficiency of the TESS system is 57.5% after 12 h waiting duration. CO and HC emissions decrease about 64% and 15%. respectively, with effect of pre-heating engine at cold start and warming-up period. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Internal combustion engine; Pre-heating; Thermal energy storage; Phase change materials; Cold-start emissions; CATALYST; BEHAVIOR